PENGHAPUSAN INFORMASI DAN/ATAU DOKUMEN ELEKTRONIK SEBAGAI BENTUK PERLINDUNGAN HUKUM KORBAN CYBERBULLYING (STUDI KOMPARATIF HUKUM INDONESIA DENGAN KOREA SELATAN) - Zahrani Salsabila (2023)
Indonesia and South Korea have legal policies regarding cyberbullying. Indonesia in Law Number 19 of 2016 contained Amendments to Law Number 8 of 2011 concerning Information and Electronic Transactions and South Korea in the Network Act. One of them is in terms of the right to be forgotten. The purpose of this study is to find out the legal policies regarding cyberbullying in Indonesia and South Korea, the forms of legal protection, the fulfillment of the right to be forgotten and so that Indonesia can have legal arrangements that side with the victim as a form of protection for victims of cyberbullying. This research is normative juridical law research complemented by interviews using comparative, statutory, and conceptual approaches. The results of this study indicate that Indonesia has not been able to exercise the right to be forgotten in handling cyberbullying because there needs to be a precise mechanism in its legal policies. In addition, the lack of socialization regarding the implementation of the right to be forgotten for victims of cyberbullying causes low public awareness in reporting. Therefore, strategic steps are needed, such as the issuance of a Ministerial Regulation regarding the mechanism for deletion, the existence of a particular complaint service made by information and communication system operators in the form of websites, applications, and contact persons, as well as conducting outreach and education to the public, so they want to report on acts cyberbullying.